Computer music modeling and retrieval: sense of sounds : 4th International Symposium, CMMR 2007, Copenhagen, Denmark, August 27-31, 2007 : revised papers Symposium, CMMR 2007, Copenhagen, Denmark, August 2007, Revised Papers - Kronland-Martinet, Richard (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Computer Music Modeling and Retrieval Symposium, CMMR 2007, held in Copenhagen, Denmark, in August 2007 jointly with the International Computer Music Conference 2007, ICMC 2007. The 33 revised full papers presented were carefully selected during two rounds of reviewing and improvement. Due to the interdisciplinary nature of the area, the papers address a broad variety of topics in computer science and engineering areas such as information retrieval, programming, human computer interaction, digital libraries, hypermedia, artificial intelligence, acoustics, signal processing, etc. CMMR 2007 has put special focus on the Sense of Sounds from the synthesis and retrieval point of view. This theme is pluridisciplinary by nature and associates the fields of sound modeling by analysis, synthesis, perception and cognition.